2002
DOI: 10.3171/spi.2002.97.3.0350
|View full text |Cite
|
Sign up to set email alerts
|

Beta—tricalcium phosphate as a substitute for autograft in interbody fusion cages in the canine lumbar spine

Abstract: Object. An interbody fusion cage has been introduced for cervical anterior interbody fusion. Autogenetic bone is packed into the cage to increase the rate of union between adjacent vertebral bodies. Thus, donor site—related complications can still occur. In this study a synthetic ceramic, β—tricalcium phosphate (TCP), was examined as a substitute for autograft bone in a canine lumbar spine model. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Different animal species have also been used to evaluate bone substitutes. For instance, in vivo studies have been conducted in rats, 10,15,20 rabbits, 8,16,[21][22][23][24][25] dogs, 13,26,27 sheep, 9 and goats. 28 As these animals are different in terms of their metabolisms and bone physiology, direct and strict comparison between all these studies is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Different animal species have also been used to evaluate bone substitutes. For instance, in vivo studies have been conducted in rats, 10,15,20 rabbits, 8,16,[21][22][23][24][25] dogs, 13,26,27 sheep, 9 and goats. 28 As these animals are different in terms of their metabolisms and bone physiology, direct and strict comparison between all these studies is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…6. In our previous study, 16) the interbody fusion cages filled with -TCP demonstrated comparable efficacy to the cages with autogenous bone in the fusion rate of union between adjacent vertebral bodies. It has been reported that BMP can induce de novo bone formation in subcutaneous sites in the absence of marrow elements.…”
Section: Biomechanical Analysismentioning
confidence: 76%
“…15) Some of them have been used clinically and have given acceptable surgical results. In our previous study, 16) synthetic beta-tricalcium phosphate (Ca 3 (PO 4 ) 2 ) (-TCP) was examined. It gave good outcomes as autogenous bone in the examinations of microradiographs and histological sections.…”
Section: Introductionmentioning
confidence: 99%
“…However, β-TCP has seldom been used alone in anterior spinal fusion. Among the limited publications describing the use of β-TCP alone in anterior spinal fusion in animal studies, the results have varied [20,26]. In our previous study, β-TCP provided poorer bone formation in comparison with autograft in an anterior spinal fusion model (H. Li et al submitted for publication).…”
mentioning
confidence: 92%